2022
DOI: 10.1177/03000605221139667
|View full text |Cite
|
Sign up to set email alerts
|

Osteoperiosteal decortication and bone grafting combined with wave plating for femoral shaft aseptic atrophic nonunion after intramedullary nailing

Abstract: Objective Femoral shaft nonunion after intramedullary nailing fixation remains a challenge for orthopedic surgeons. This study evaluated osteoperiosteal decortication and iliac bone grafting combined with wave plating as a treatment for aseptic atrophic nonunion of the femoral shaft after intramedullary nailing. Methods The study included 22 patients (two female, 20 male; mean age 40.8 years [range, 19–61]) with aseptic atrophic nonunion of the femoral shaft who underwent osteoperiosteal decortication and ilia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…In our experience, extensive removal of inactive cortical bone could refresh the nonunion site, resulting in large bone defects. Other studies 17 , 27 , 28 have used a decortication technique to remove fibrous tissue and sclerotic bone at the nonunion site, but this method lacks clear standardization and relies mainly on a surgeon's personal experience. To overcome these challenges and avoid large bone defects, our study utilized a hybrid bone grafting technique that simplifies the process and provides greater standardization.…”
Section: Discussionmentioning
confidence: 99%
“…In our experience, extensive removal of inactive cortical bone could refresh the nonunion site, resulting in large bone defects. Other studies 17 , 27 , 28 have used a decortication technique to remove fibrous tissue and sclerotic bone at the nonunion site, but this method lacks clear standardization and relies mainly on a surgeon's personal experience. To overcome these challenges and avoid large bone defects, our study utilized a hybrid bone grafting technique that simplifies the process and provides greater standardization.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 558 of 611 patients (96.3%) achieved bone consolidation, in a mean time of 8.26 ± 6.12. A complete (100%) bone healing was reported in 10 studies [13,[16][17][18][19][20][23][24][25]28]; in three studies, bone healing rate was reported between 95% and 100% [15,22,27]; and in three studies, bone healing rate was less than 95% [14,21,26].…”
Section: Discussionmentioning
confidence: 99%
“…Of the 16 studies selected, 14 were retrospective [13][14][15][16][17][18][19][20][21][22][23][24][25][26] and 2 were prospective [27,28]. Overall, data from 632 patients were analyzed in our systematic review (summarized data are reported on Table 1).…”
Section: Demographicsmentioning
confidence: 99%
See 1 more Smart Citation